Method for Increasing Students' Interest in Reading via Literacy Activities at SDN 96 Palembang - Arni, Yusni; Kesuma, Rama Medi; Anggraini, Monalika (Pusdikra Publishing, 2024)
There are references in this exploration. The sources of data were papers published in scientific publications. Content analysis was used to examine this content. Reading fifteen twinkles before class, having a reading niche, and establishing a textbook-rich atmosphere are some of the knowledge enterprise used at SDN 96 Palembang to encourage early reading. We created fifteen- nanosecond reading assignments before to class, made library visits essential, and enhanced journaling and other reading chops during the growth phase. reading that takes place at the launch, middle, or finish of a library literacy phase that spans a set quantum of time and involves the use of a variety of coffers and technologies. Supporting variables include student enthusiasm, instructor encouragement, availability of facilities and infrastructure, adequate funds, active involvement of the school community, and parental support for educational initiatives. Lack of enthusiasm of students, ignorance of teachers about the value of reading and writing, their physical limitations and inadequate school facilities are some of the things that hinder.